ABAP1 Plays a Role in the Differentiation of Male and Female Gametes in Arabidopsis thaliana - Cabral, Luiz M.; Masuda, Hana P.; Ballesteros, Helkin F.; de Almeida-Engler, Janice; Alves-Ferreira, Márcio; De Toni, Karen L. G.; Bizotto, Fernanda M.; Ferreira, Paulo C. G.; Hemerly, Adriana S. (Frontiers in Plant Science, 2021)
The correct development of a diploid sporophyte body and a haploid gametophyte relies on a strict coordination between cell divisions in space and time. During plant reproduction, these divisions have to be temporally and spatially coordinated with cell differentiation processes, to ensure a successful fertilization. Armadillo BTB Arabidopsis protein 1 (ABAP1) is a plant exclusive protein that has been previously reported to control proliferative cell divisions during leaf growth in Arabidopsis. Here, we show that ABAP1 binds to different transcription factors that regulate male and female gametophyte differentiation, repressing their target genes expression. During male gametogenesis, the ABAP1-TCP16 complex represses CDT1b transcription, and consequently regulates microspore first asymmetric mitosis. In the female gametogenesis, the ABAP1-ADAP complex represses EDA24-like transcription, regulating polar nuclei fusion to form the central cell. Therefore, besides its function during vegetative development, this work shows that ABAP1 is also involved in differentiation processes during plant reproduction, by having a dual role in regulating both the first asymmetric cell division of male gametophyte and the cell differentiation (or cell fusion) of female gametophyte.